General method for the synthesis of enaminones via photocatalysis - Paula Pérez-Ramos; Raquel G. Soengas; Humberto Rodríguez-Solla (Beilstein Journal of Organic Chemistry)
Enaminones are key intermediates in the synthesis of several derivatives with important applications in medicinal chemistry. Furthermore, many marketed drugs feature the enaminone structural moiety. In this context, we have developed a photoredox and nickel catalytic system to rapidly forge the enaminone scaffold from 3-bromochromones via a Michael reaction of an amine with an electron-deficient alkene moiety and subsequent photocatalyzed debromination. With this dual catalytic system, a range of structurally diverse enaminone derivatives have been achieved in good yields with total trans selectivity. Mechanistic studies indicate that the key to the success of this process is the formation of an unexplored ternary Ni-complex with 3-bromochromone and a pyridinium salt, which is crucial for the effective activation of the α,β-unsaturated system towards the nucleophilic addition.